The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1002/tox.23704
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the BNIP3/NIX‐dependent mitophagy aggravates copper‐induced mitochondrial dysfunction in duck renal tubular epithelial cells

Abstract: The accumulation of copper (Cu) in the organisms could lead to kidney damage by causing mitochondrial dysfunction. Given that mitochondria are one of the targets of Cu poisoning, this study aimed to investigate the role of mitophagy in Cu‐induced mitochondrial dysfunction in renal tubular epithelial cells to understand the mechanism of Cu nephrotoxicity. Hence, the cells were treated with different concentrations of Cu sulfate (CuSO4) (0, 100, and 200 μM), and mitophagy inhibitor (Cyclosporine A, 0.5 μM) and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Studies have demonstrated that various types of mitophagy-related receptors in mammalian cells can mediate this process. Mitochondrial swelling, vesicle formation, and somatic cristae breakage were observed in the CuSO4-induced kidney injury model, nip3-like protein (NIX)/BNIP3 mRNA and protein levels were significantly upregulated, and the number of mitochondrial and lysosomal fluorescent aggregation sites was increased, suggesting that CuSO4 treatment promotes the onset of BNIP3/NIX-mediated mitophagy, and that co-treatment with CuSO4 and an inhibitor of mitophagy significantly exacerbates mitochondrial dysfunction ( Bai et al, 2023 ). Focused low-intensity pulsed ultrasound (FLIPUS) treatment significantly enhanced the protein level of phosphoglycerate mutase 5 (PGAM5) in interleukin-1β (IL-1β)-induced primary mouse chondrocytes of knee joints, promoted Ser13 dephosphorylation containing FUN14 do domain protein 1 (FUNDC1), activated mitophagy in chondrocytes, significantly upregulated the expression of collagen II (Col II) and B-cell lymphoma/leukemia-2 (Bcl-2), downregulated matrix metalloproteinase 13 (MMP13), Bcl-2 associated X protein (Bax), and cleaved caspase-3 expression, and attenuated extracellular matrix (ECM) degradation and apoptosis.…”
Section: Overview Of Mitophagymentioning
confidence: 99%
“…Studies have demonstrated that various types of mitophagy-related receptors in mammalian cells can mediate this process. Mitochondrial swelling, vesicle formation, and somatic cristae breakage were observed in the CuSO4-induced kidney injury model, nip3-like protein (NIX)/BNIP3 mRNA and protein levels were significantly upregulated, and the number of mitochondrial and lysosomal fluorescent aggregation sites was increased, suggesting that CuSO4 treatment promotes the onset of BNIP3/NIX-mediated mitophagy, and that co-treatment with CuSO4 and an inhibitor of mitophagy significantly exacerbates mitochondrial dysfunction ( Bai et al, 2023 ). Focused low-intensity pulsed ultrasound (FLIPUS) treatment significantly enhanced the protein level of phosphoglycerate mutase 5 (PGAM5) in interleukin-1β (IL-1β)-induced primary mouse chondrocytes of knee joints, promoted Ser13 dephosphorylation containing FUN14 do domain protein 1 (FUNDC1), activated mitophagy in chondrocytes, significantly upregulated the expression of collagen II (Col II) and B-cell lymphoma/leukemia-2 (Bcl-2), downregulated matrix metalloproteinase 13 (MMP13), Bcl-2 associated X protein (Bax), and cleaved caspase-3 expression, and attenuated extracellular matrix (ECM) degradation and apoptosis.…”
Section: Overview Of Mitophagymentioning
confidence: 99%